A methodology for the design of sections block length on ETCS L2 railway networks. (May 2020) - Vignali, Valeria; Cuppi, Federico; Lantieri, Claudio; Dimola, Nicola; Galasso, Tomaso; Rapagnà, Luca
Abstract: This paper presents an analytical-based methodology that computes the optimal length of block sections and the marker boards' location following headway requirements, with the lowest amount of signalling equipment, for an ETCS L2 railway networks. It is applied to the Danish Fjernbane Infrastructure East project, which aims at replacing the existing signalling system with a new one based on ETCS Level 2. Starting from track layout, rolling stock information and headway scenario, and knowing the trains features, an easy backward calculation, using OpenTrack tool, defines the first signalling equipment position (i.e. Marker Boards, Axle Counter) to fulfil the headway requirements. The application to the main passenger and freight lines in Danish Fjernbane Infrastructure East area shows the significance of the proposed methodology able to define a robust signalling configuration which also provides a satisfying trade-off between total cost and railway operational performance. Highlights: An analytical-based methodology that computes the optimal length of block sections on ETCS L2 railways has been proposed. Starting from track layout, rolling stock, headway scenario, a backward calculation defines signalling equipment position. The application to lines in Danish Fjernbane Infrastructure East area shows the significance of the proposed methodology.